Prognosis of primary sclerosing cholangitis according to age of onset. (15th April 2021) - Watanabe, Takeo; Nakai, Yousuke; Mizuno, Suguru; Hamada, Tsuyoshi; Kogure, Hirofumi; Hirano, Kenji; Akamatsu, Nobuhisa; Hasegawa, Kiyoshi; Isayama, Hiroyuki; Koike, Kazuhiko
Abstract: Background: Liver failure and biliary tract cancer (BTC) are major life‐threatening events in the clinical course of primary sclerosing cholangitis (PSC). Although these are competing events, they are typically evaluated as a composite prognostic endpoint. In Japan, the clinical characteristics and prognosis of PSC reportedly differ according to age of onset. We compared the prognosis of younger‐ versus older‐onset PSC by competing risk analysis. Methods: This was a retrospective analysis of 144 patients with PSC who were followed up for a median of 6.7 years. The patients were divided into two groups according to a cutoff age of onset of 44 years. We compared the prognosis of younger‐onset PSC (n = 91) and older‐onset PSC (n = 53) by competing risk analysis, incorporating mortality related and that unrelated to BTC as competing events. Results: There was no difference in BTC‐related mortality between patients with younger‐onset and those with older‐onset PSC (subdistribution hazard ratio [SHR], 0.89; 95% confidence interval [CI], 0.17‐4.56, P  = .888). The cumulative incidence of mortality due to other causes, including liver transplantation and liver failure, was non‐significantly higher in patients with older‐onset PSC (SHR, 1.58; 95% CI, 0.88‐2.84; P  = .129). Conclusions: Although we did not find a significant difference in prognosis by onset age, patients with older‐onset PSC had worse liver‐transplantation‐free survival than those with younger‐onset PSC. A large cohort study is needed to evaluate the clinical outcomes of older‐ and younger‐onset PSC. Abstract : Highlight Watanabe and colleagues compared the outcomes of primary sclerosing cholangitis by onset age, incorporating mortality related and unrelated to biliary tract cancer. While biliary tract cancer‐unrelated mortality was non‐significantly associated with older‐onset primary sclerosing cholangitis, there was no difference in biliary tract cancer‐related mortality between the older‐ and younger‐onset groups.